Answer:
![{f}^{ - 1} (f(93)) = 93](https://tex.z-dn.net/?f=%7Bf%7D%5E%7B%20-%201%7D%20%28f%2893%29%29%20%3D%2093)
![f(f(7)) = - 15](https://tex.z-dn.net/?f=f%28f%287%29%29%20%3D%20%20-%2015)
Step-by-step explanation:
A function and its inverse has the following properties
![{f}^{ - 1} (f(x)) = x](https://tex.z-dn.net/?f=%20%7Bf%7D%5E%7B%20-%201%7D%20%28f%28x%29%29%20%3D%20x)
This implies that;
![{f}^{ - 1} (f(93)) = 93](https://tex.z-dn.net/?f=%20%7Bf%7D%5E%7B%20-%201%7D%20%28f%2893%29%29%20%3D%2093)
From the table,
![f(7) = - 6](https://tex.z-dn.net/?f=f%287%29%20%3D%20%20-%206)
This means that:
![f(f(7)) = f( - 6)](https://tex.z-dn.net/?f=f%28f%287%29%29%20%3D%20f%28%20-%206%29)
![f(f(7)) = - 15](https://tex.z-dn.net/?f=f%28f%287%29%29%20%3D%20%20-%2015)
Note that: f(7) means the value of f(x) when x=7.
From the table f(x)=-6 when x=7.
That is why f(7)=-6.
You have to use the Pythagorean theorem a squared plus b squared is c squared so 13 squared plus 18 squared equals c squared. 13x13=169 18x18=324 169+324=493 so c squared is 493 to get c you square root 493 which equals 22.2 so the diagonal, c, is 22.2 centimeters long
Answer:
-4( 4x^2 -y^2)
Step-by-step explanation:
so I did the step on the paper
first line : is the equation itself
2nd line : I multiple the term in the parentheses together
3rd line: I multiple the - 2 to the term I got
4th line : I simplify it
Answer:
look up mixed numbers calculator by calculator soup, and then you can find all of your answers! Its an amazing website! good luck (:
Step-by-step explanation: